HUBUNGAN SELF-CONTROL DENGAN HASIL BELAJAR SISWA DI MAN 2 PADANG PANJANG MASA PANDEMI - Lili Sri Diana Rkt; Muhiddinur Kamal; Afrinaldi; Budi Santosa (Universitas Pahlawan Tuanku Tambusai, 2022)
This research departs from the phenomenon where it is seen that most of the students at school in self-control are very weak for the learning process. Students who cannot control themselves in learning become lazy to take part in learning such as not participating in the online learning process, just busy with other sites, lazy to do the assignments given by the subject teacher and students assume that online learning is trivial. So many student learning outcomes decreased drastically because they could not control themselves. This research is classified as a correlational quantitative research. The population is all students of MAN 2 Padang Panjang class X IPS, XI IPS, XII IPS. However, the researcher only took the population from class XI IPS 1 with a sample of 30 students. Here the researcher uses a questionnaire because this research is a quantitative research. The data analysis technique uses simple statistics, and in correlating research variables using Statiscal Product and Service Solution (SPSS) 2024. Based on the calculation results, it can be seen that rcount 0.436 <rtable 0.361, it can be concluded that there is a correlation between variable X and Variable Y, namely between self- control of student learning outcomes. Meanwhile, Fcount is 4.226 while Ftable is equal to, meaning 4.226 > 3.64. Based on the calculation of the criteria above, it can be concluded that Ho is rejected and Ha is accepted, meaning that there is the effect of self-control on student learning outcomes at MAN 2 Padang Panjang. The coefficient of determination shows that the contribution of self-control to student learning outcomes is 19% and 81% is influenced by other factors that are not included in the author's research variables. Based on the research findings, there is a relationship between self-control and learning outcomes where both have a positive and significant relationship. Thus, the better self-control in students, the better student learning outcomes, on the contrary, the less self-control in students, the lower student learning outcomes. Keywords:Self-Control, Learning Outcomes